2019
DOI: 10.1186/s10033-019-0319-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cross-Sectional Flow Area of Annular Volute Casing on Transient Characteristics of Ceramic Centrifugal Pump

Abstract: The annular volute is typically used in a slurry pump to reduce the collisions between solid particles and the volute tongue and to achieve a better resistance to blocking. However, only limited studies regarding annular volutes are available, and there is no systematic design method for annular volutes. In this study, the influence of volute casing cross-sectional flow area on the hydraulic loss, pressure pulsations, and radial force under varying working conditions in a centrifugal ceramic pump are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These results are in agreement with that reported in Ref. [19][20][21]. As we all know, the radial gap between impeller outlet and volute tongue exerts a great influence on the pressure fluctuation and hydraulic characteristics of the centrifugal pump.…”
Section: Introductionsupporting
confidence: 93%
“…These results are in agreement with that reported in Ref. [19][20][21]. As we all know, the radial gap between impeller outlet and volute tongue exerts a great influence on the pressure fluctuation and hydraulic characteristics of the centrifugal pump.…”
Section: Introductionsupporting
confidence: 93%
“…Especially when studying the flow problem of complex flow field, the use of CFD simulation technology has lower •4• cost, shorter cycle time than the solid model test, and the calculation accuracy can meet the engineering requirements, which has become an important method of flow fields analysis [22][23]. In fact, CFD simulation technology has been widely used in engineering [24][25][26]. Computational fluid dynamics models based on the Navier-Stokes equation are widely used to solve the motion characteristics of fluids in hydraulic pumps.…”
Section: Cfd Simulationmentioning
confidence: 99%
“…Nouha et al [22] found that the pump dynamic behavior with the impeller geometry during the starting periods. Tao et al [23] found that the increase in the volute casing flow area is helpful to improve the operation stability of the pump. Wang et al [24] found that the valve head change during the startup process had a significant transient effect.…”
Section: Introductionmentioning
confidence: 99%